The Impact Of Implementing Legislation For Individuals Who Commit Crimes In The Marine Environment Is Currently Being Assessed - Kumalasari, Dewi Ratih (PT. Anagata Sembagi Education, 2024)
This research is entitled Legal Sanctions for Perpetrators of Marine Ecosystem Crime because they want to emphasize that everyone, both individuals and corporations, who commit environmental damage, especially marine ecosystems, must be responsible for their actions and be ready to face criminal sanctions in accordance with statutory regulations. This research uses normative juridical legal research methods, using three approaches: statute approach, conceptual approach, and case approach. The research materials used in this research are primary and secondary legal materials. In writing this article, deductive analysis was used to organize data and research. This method of investigation is based on general principles to explain specific events or general theories based on concrete facts. The aim of this research is to find and analyze law enforcement against individuals who commit violations of destroying marine ecosystems. The research findings indicate that countries are responsible for preserving marine ecosystems through effective regulation and law enforcement. However, the implementation of these regulations still faces challenges, such as limited resources and coordination among agencies. The study provides recommendations to strengthen the role of countries in preserving marine ecosystems, including enhancing institutional capacity, strengthening law enforcement, and forming partnerships with the private sector and communities